Hubungan Kualitas Tidur dengan Peningkatan Tekanan Darah pada Lansia - Kurniadi Kurniadi (Jurnal Surya Medika (JSM), 2022)
In general, the older you get, the greater the risk of hypertension. The phenomenon obtained by many elderly patients with hypertension complains of difficulty sleeping, often wakes up at night so that it has an impact on blood pressure accompanied by complaints of dizziness and weakness when waking up in the morning. This study aims to determine the "Relationship of Sleep Quality With Increased Blood Pressure in the Elderly". This research method uses the method Literature Review. In this study, there are 6 journals that have been screened with criteria inclusion ranging from a sample of 22-107 respondents, with 1 study design, namely cross-sectional, a journal published in 2017-2020 and using Indonesian. Obtained 6 research results according to the inclusion criteria. The research sample averaged 22-107 respondents, and the results of the research in 6 journals were in agreement, which showed that there was a relationship between sleep quality and increased blood pressure in the elderly, which showed a p-value <0.05. Poor sleep quality can affect and make it easier for the elderly to experience increased blood pressure, it is hoped that the elderly can prevent hypertension by routinely checking blood pressure, routine treatment, and living a healthy lifestyle, such as avoiding high salt intake patterns, exercising. exercise and to prevent ongoing sleep disturbances the elderly can manage their sleep schedule well.